2016
DOI: 10.1200/jco.2016.34.15_suppl.e18203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of provider volume on outcomes of patients with Hodgkin lymphoma.

Abstract: Background: While the provider volume-outcome relationship has been established for many complex surgeries and invasive procedures, the provider volume impact on outcomes for Hodgkin lymphoma (HL) is less certain. We hypothesized that high-volume providers (HVPs) may have superior outcomes compared with low-volume providers (LVPs). Methods: We performed a chart-based, retrospective review of all patients receiving adriamycin, doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) for HL at the West Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Using the NCDB, we found that patients with Hodgkin lymphoma managed at high-volume centers (9 or more patients per year) had approximately 20% lower mortality than those managed at low-volume centers, and this persisted even after adjustments for patientand disease-related factors. 18 The authors found that low-volume providers (providers treating fewer than 3 patients with Hodgkin lymphoma annually) were more likely to hold chemotherapy doses for afebrile neutropenia. Furthermore, the impact of a higher volume on lower mortality did not attain a ceiling at 9 patients per year, as was evidenced by continual improvement as the volume increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the NCDB, we found that patients with Hodgkin lymphoma managed at high-volume centers (9 or more patients per year) had approximately 20% lower mortality than those managed at low-volume centers, and this persisted even after adjustments for patientand disease-related factors. 18 The authors found that low-volume providers (providers treating fewer than 3 patients with Hodgkin lymphoma annually) were more likely to hold chemotherapy doses for afebrile neutropenia. Furthermore, the impact of a higher volume on lower mortality did not attain a ceiling at 9 patients per year, as was evidenced by continual improvement as the volume increased.…”
Section: Discussionmentioning
confidence: 99%
“…These results also show that the mortality for facilities treating fewer than 9 patients per year (Q1-Q3) was similar. 18 Moreover, low-volume providers were more likely to prescribe dose delays than their counterparts. Our study also found that the majority of high-volume facilities were academic centers and research programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation